Absorption Spectra Comparison of Tm/Ho-Codoped Bototellurite Glasses - Azmi Saraswati; Ahmad Marzuki; Venty Suryanti (Journal of Physics: Theories and Applications, 2021)
This paper presents a comparison study of absorption spectra of borotellurite glasses with compostion: 20TeO2 – 15Bi2O3 – 3TiO2 – (4-x) Na2CO3 – 1Tm2O3 - xHo2O3 where x = 0; 0.5; 1; 1.5; 2; 2.5 (mol%). All glasses are fabricated using melt quenching method. Absorption spectra were recorded at room temperature in the spectral range of 200 – 1100 nm. Within this range, glass with x = 0 mol % of Ho2O3 shows 2 absorption peaks which corresponds to electronics transition from 3H6 to state to 3F3 and 3H4.   For x = 0.5; 1; 1.5; 2; 2.5 (mol%), nine absorption peaks corresponding to electronics transition from 3H6 to state to 5G5, 5G6, 1G4, 1G4, 5F3, 5F4, 5F5, 3F3, and 3H4 are shown. It is shown that absorption at 680 nm and 790 are insensitive to the addition of Ho2O3 in contrast to that at 580 nm and 650 nm.